Peran Aktif Masyarakat dalam Kegiatan Kuliah Subuh di Masjid Al-Muhajirin Desa Cahaya Negeri Seluma - Natya Nugrah; Niza Azwarita; Angelia Maharani; Fadilah Nur Zakirah; Wicki Widiarti; Ayu Puspita Sari; Bintang Cahyadi; Pattria Sepita; Ahmad Ilham Romaidon Sipahutar (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
In the Kuliah Kerja Nyata (KKN) program, the role of the community in carrying out morning prayers at the mosque and morning lectures is the purpose of this study. This study was conducted in Cahaya Negeri Village where Al-Muhajirin mosque is an important part of the community and shows that supporting and participating in the morning prayer activity at the mosque is very important. The Mosquemosque is a place where people do activities, and the morning prayers are an important part of the religious life of the community. This study shows that people should be given the opportunity to participate more actively in organizing and managing the morning prayers and religious lectures at the mosque.